Long-term outcomes of initially conservatively treated midshaft clavicle fractures - Lee, Gwan Bum (Clin Shoulder Elb, 2021)
BACKGROUND: Recent studies about completely displaced midshaft clavicle fractures have reported that their nonunion/malunion rates were significantly higher in conservatively treated patients compared to surgically treated patients. The purpose of this study was to evaluate the factors associated with treatment decisions for midshaft clavicle fractures and also the factors that affect patient satisfaction with their treatment choice. METHODS: We retrospectively reviewed the records of 75 patients who had been diagnosed with a midshaft clavicle fracture and were treated conservatively at a single institution between March 1, 2013, and December 31, 2014. Their medical records were reviewed to investigate the severity of the initial vertical displacement. A telephone survey was carried out to identify the presence of any patient-perceived deformity and determine if the patient eventually underwent surgery and whether the patient would prefer surgery if the injury recurred. RESULTS: Significantly more patients with vertical displacement ≥100% (9/28) eventually underwent surgery compared to patients with vertical displacement <100% (3/32, p=0.028). Patients with vertical displacement ≥100% (13/28) were significantly more likely to prefer surgery compared to patients with vertical displacement <100% (7/32, p=0.044). Among the conservatively treated patients, nine of 32 participants with a patient-perceived deformity and one of 16 without a patient-perceived deformity responded that they would prefer to receive surgery in same situation in the future (p=0.079). CONCLUSIONS: Patients with a midshaft clavicle fracture with vertical displacement of ≥100% may eventually require surgical treatment. When conservative treatment is carried out, the long-term patient results may be unsatisfactory due to perceived residual deformities.